(3GdMb GdeHjf aj JUhjH QCj GdeLJgOjf hJNWFI GdENHGQjjfs - (3GdMdj, GdLfGLj, GdfLaj, ef Bd cGTa GdZWGA, LYaQ Hf NVQ Hf TdGd, J (B1227 (3g`s ((3eMeO LeGd GdgGTejs)
(3ChdgG (B:s
(3GdMeO ddg GdPj GdEfSGf hYdeg GdHjGf(B... (3hHYO, aEfg bGeJ GdMQH Ydi SGb hGMOI hcKQ GdLOGd (B... (3hHSHH Pdc GfbSehG Edi bSejf eLJgOjjf hENHGQjjf(B...s
(3BNQgG (B:s
(3haj GdhUGjG hGdSLdGJ hLejY GdNWGHGJ GdhVYjGJ ceG dG jNais
(3efbhdI ef fSNI GdeDdas
(3JHUQI GdeDda (B:s
(3aj SfI haGJg GNJdGa(B: 1228(3, h(B: 1227(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B2(3, U(B124s
(3GdPQjYI HQbe(B: 190s
Keywords: (3GdJhMjO hGdedd hGdfMds